2013
DOI: 10.1002/cjce.21923
|View full text |Cite
|
Sign up to set email alerts
|

Particles deposition at horizontal flat plate in turbulent particulate flow

Abstract: The deposition of aluminium oxide 12 and 23 μm particles onto a horizontal flat plate within the laminar boundary layer in the free‐stream moderate turbulent flow was studied. The present numerical model considered the deposition onto the surface to be a probabilistic process determined both by hydrodynamics and the adhesive behaviour of particles and surface. Numerical simulation was realised for the flat‐plate laminar boundary layer. The two‐fluid approach was used for writing the Euler equations for a carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Villalba et al (2012) revealed the weak tendency of particles aligning in the streamwise direction, even if they were released homogeneously into the flow field. For the further review, see Monchaux et al (2012), Uchiyama and Shimada (2014), and Kartushinsky et al (2014). The above researches were mainly performed in wall turbulence without considering the wall permeability and its effects on particle dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Villalba et al (2012) revealed the weak tendency of particles aligning in the streamwise direction, even if they were released homogeneously into the flow field. For the further review, see Monchaux et al (2012), Uchiyama and Shimada (2014), and Kartushinsky et al (2014). The above researches were mainly performed in wall turbulence without considering the wall permeability and its effects on particle dispersion.…”
Section: Introductionmentioning
confidence: 99%